2022
DOI: 10.1039/d1cp05175j
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase protonated nicotine is a mixture of pyridine- and pyrrolidine-protonated conformers: implications for its native structure in the nicotinic acetylcholine receptor

Abstract: The infrared (IR) spectra of gas phase protonated nicotine has been measured in the never-before probed N-H “fingerprint region” (3,200–3,500 cm−1). The protonated molecules generated by an electrospray source are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
40
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(48 citation statements)
references
References 39 publications
5
40
3
Order By: Relevance
“…3,5 Aqueous NOR is known to be protonated also at the pyrro nitrogen (Pyrro-NORH + ), whereas recent investigations of gas-phase NOR suggested that it is almost fully protonated at the pyri nitrogen (Pyri-NORH + ). 18,24 NOR's protomer stability is environment dependent, although the effect of the environment on NOR's protonation site appears to be more extreme than that of NIC.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…3,5 Aqueous NOR is known to be protonated also at the pyrro nitrogen (Pyrro-NORH + ), whereas recent investigations of gas-phase NOR suggested that it is almost fully protonated at the pyri nitrogen (Pyri-NORH + ). 18,24 NOR's protomer stability is environment dependent, although the effect of the environment on NOR's protonation site appears to be more extreme than that of NIC.…”
supporting
confidence: 83%
“…While previous gas phase studies 24 have been able to capture protomer distributions at RT, the present experiments are limited by the dissociation process. These previous studies 24 have indicated that kinetic trapping at low temperatures prevents equilibrium, and for this reason the temperature in the present experiments is modulated to achieve thermal equilibrium and to be able to observe the hydrated clusters. The present work focuses on singly hydrated clusters, which can be observed well above any suspected kinetic trapping.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Cryogenic infrared photodissociation spectra of H 2 tagged nicotineH + ions provide additional spectroscopic evidence for the presence of both nicotineH + protomers. 198 Another example of FAIMS separation of protomer ions is the case of quinazolineH + where two protomers present from ESI in comparable yields. 190 With FAIMS separation, the spectra of both protomers were separately recorded, with a vibronic structure (Fig.…”
Section: Ion Mobility Spectrometry With Photodissociationmentioning
confidence: 99%